Pengaruh Self Esteem, Self Efficacy, Kinerja Pegawai Terhadap Kepuasan Pegawai Pada Badan Pengelola Keuangan Dan Aset Daerah Kota Metro - Suwarto, Suwarto; Yateno, Yateno; Saraswati, Eka (Universitas Muhammadiyah Metro, 2023)
The influence of globalization today will lead to increasingly global competition. Human resources, namely employees or employees have an important role in a company. The existence of competent and quality human resources will support the company's activities and are assets that must be guarded by the company to be managed and managed. This study aims to determine the relationship between slef esteem and employee satisfaction at BPKAD metro city. Knowing the effect of self efficacy on job satisfaction of employees at BPKAD metro city, knowing the effect of employee performance on job satisfaction at BPKAD in metro city, knowing the effect of slef esteem, slef efficacy of employee performance, on employee job satisfaction at BPKAD Metro city. The sample of respondents in this study were employees of the financial and asset management agency of the Kora metro area, totaling 60 people, using the accideal sampling technique. The quantitative method in this study used a quantitative approach. n comparative. The data were collected in questionnaire sheets and analyzed using multiple linear regression analysis. The results of this study showed that the self-esteem variable obtained a tcount value of 0.315 ttable <234 with a significant value of 0.754 <0.05, meaning that the quality of self-esteem has an effect on employee satisfaction. tcount 18.905 ttable <234 with a significant value of 0.00 <0.05, meaning that the quality of self-efficacy affects employee satisfaction. tcount -0.315 ttable <234 with a significant value of 0.754 <0.05, meaning that the quality of self-efficacy has no effect on employee satisfaction. While in the f-test (both test fcount 865.963 and ftable 2.77 that the independent variables jointly influence positive and significant employee satisfaction. This means that self-esteem (x1), self-efficacy (x2), employee performance (3), employee satisfaction (y) the independent variable is able to explain the independent variable of 98.1% while the remaining 1% is influenced by the variable which were not included in this study.